Mycorrhizal inoculation effects on growth and the mycobiome of poplar on two phytomanaged sites after 7-year-short rotation coppicing - Ciadamidaro, Lisa; Pfendler, Stéphane; Girardclos, Olivier; Zappelini, Cyril; Binet, Philippe; Bert, Valerie; Khasa, Damase; Blaudez, Damien; Chalot, Michel (Frontiers in Plant Science, 2022)
Aims Afforestation of trace-element contaminated soils, notably with fast growing trees, has been demonstrated to be an attractive option for bioremediation due to the lower costs and dispersion of contaminants than conventional cleanup methods. Mycorrhizal fungi form symbiotic associations with plants, contributing to their tolerance towards toxic elements and actively participating to the biorestoration processes. The aim of this study was to deepen our understanding on the effects of mycorrhizal inoculation on plant development and fungal community at two trace-element contaminated sites (Pierrelaye and Fresnes-sur-Escaut, France) planted with poplar (Populus trichocarpa x Populus maximowiczii). Methods The 2 sites were divided into 4 replicated field blocks with a final plant density of 2200 tree h-1. Half of the trees were inoculated with a commercial inoculum made of a mix of mycorrhizal species. The sites presented different physico-chemical characteristics (e.g., texture: sandy soil versus silty-loam soil and organic matter: 5.7% versus 3.4% for Pierrelaye and Fresnes-sur-Escaut, respectively) and various trace element contamination levels. Results After 7 years of plantation, inoculation showed a significant positive effect on poplar biomass production at the two sites. Fungal composition study demonstrated a predominance of the phylum Ascomycota at both sites, with a dominance of Geopora Arenicola and Mortierella elongata, and a higher proportion of ectomycorrhizal and endophytic fungi (with the highest values observed in Fresnes-sur-Escaut: 45% and 28% for ECM and endophytic fungi, respectively), well known for their capacity to have positive effects on plant development in stressful conditions. Furthermore, Pierrelaye site showed higher frequency (%) of mycorrhizal tips for ectomycorrhizal fungi (ECM) and higher intensity (%) of mycorrhizal root cortex colonization for arbuscular mycorrhizal fungi (AMF) than Fresnes-sur-Escaut site, which translates in a higher level of diversity. Conclusions Finally, this study demonstrated that this biofertilization approach could be recommended as an appropriate phytomanagement strategy, due to its capacity to significantly improve poplar productivity without any perturbations in soil mycobiomes.